2019
DOI: 10.1371/journal.pone.0218405
|View full text |Cite
|
Sign up to set email alerts
|

Mental fatigue impairs time trial performance in sub-elite under 23 cyclists

Abstract: Purpose This study investigates the effect of a mentally demanding response inhibitory task on time trial performance in sub-elite under 23 cyclists. Methods Ten under 23 road cyclists completed two separate testing sessions during which they performed two different cognitive tasks before completing a 30-min time trial on the cycle ergometer. In the experimental condition, 30 min of a standard cognitive task (Stroop task) was used to elicit mental fatigue; in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 32 publications
(49 reference statements)
0
38
1
Order By: Relevance
“…Our recent research seems to support this hypothesis, showing that tolerance to mental exertion is higher in elite athletes than in recreational ones, but also that sub-elite athletes have an intermediate ability to tolerate mental exertion compared to elite and recreational. 11,12 We found no change in cognitive performance in our untrained, yet high-functioning healthy adult participants. Exercise training interventions that target cognitive performance in young and healthy adults are rare in the literature (e.g., 25) although there is both cross-sectional 26 and randomised controlled trial 27 evidence that cognitive performance does benefit from exercise training in this population.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Our recent research seems to support this hypothesis, showing that tolerance to mental exertion is higher in elite athletes than in recreational ones, but also that sub-elite athletes have an intermediate ability to tolerate mental exertion compared to elite and recreational. 11,12 We found no change in cognitive performance in our untrained, yet high-functioning healthy adult participants. Exercise training interventions that target cognitive performance in young and healthy adults are rare in the literature (e.g., 25) although there is both cross-sectional 26 and randomised controlled trial 27 evidence that cognitive performance does benefit from exercise training in this population.…”
Section: Discussionmentioning
confidence: 54%
“…This task consisted of 90 min of computerised cognitive tasks presented on a laptop using specialist software (E-Prime, Psychology Software Tools Inc., United States). The task was divided into three parts: a) an initial 45-min cognitive battery assessing cognitive domains including working memory, response inhibition and task-switching; b) a 40-min modified incongruent Stroop colour-word task 11,12 ; and c) 5-min of the same task-switching (flanker) task as in the cognitive battery. The 45-min cognitive battery comprised four different tasks: 1) 15-min of the flanker task 13 ; 2) 10-min of a go/no-go task 14 ; 3) 10-min of a 2-back task 15 ; and 4) 10-min of a working memory task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we hypothesized executive load to reduce task-triggered valence ratings (i.e., to make them less positive), to slightly increase arousal, and to leave RPE scores unaffected, replicating the dissociation found in our previous reports. As some studies have also shown that manipulations of mental demand across conditions matched in external physical demands do not significantly influence physiological parameters like heart rate or blood lactate concentration [ 28 ], we do not expect differences in internal physical load indices across conditions.…”
Section: Introductionmentioning
confidence: 68%
“…As noted above, a computerized ST (Stroop,1935) continuum over 30 min was used as the cognitive task to induce MF in the CT condition following a procedure used in other studies (Badin et al, 2016;Filipas et al, 2019;Gantois et al, 2019;Smith et al, 2016). The ST consisted of three stages.…”
Section: Mental Fatigue and Control Treatment Conditionsmentioning
confidence: 99%